Dragon kingdom of Wrenly. Book 4, Ghost island - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly, 2021)
"Fresh off the excitement of the Night Hunt, Ruskin, Cinder, Groth, and Roke set out for a camping trip on Ghost Island, which, according to Groth, is definitely not haunted despite its name"--